Understanding the dimensions of the digital system - Islas, Octavio (2018)
Our objective is to highlight the dimensions of the digital system. To do it, we present figures related to the global penetration of the Internet and analyze the penetration of the Internet in the Americas. Then we focus our attention on social networks, and present the most significant Facebook stats. Finally, we refer the studies of the World Economic Forum, which are essential for understanding the importance of the Internet and social networks in the development of telecommunications systems.